2010
DOI: 10.4081/gh.2010.192
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal evaluation of cattle trade in Sweden: description of a grid network visualization technique

Abstract: Abstract. Understanding the intensity and spatial patterns of animal transfers is of prime importance as geographical moves play an important part in the spread and potential control of contagious animal diseases of veterinary importance. For the purpose of visualizing all registered between-herd animal movements in Sweden between 1 July 2005 and 31 December 2008 by map animation, a grid network technique based on the Bresenham line algorithm was developed. Potential spatio-temporal clustering of animals regis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 12 publications
3
16
0
Order By: Relevance
“…This confirmed that epidemic size was mainly driven by infected cattle farms. It also confirmed the expected effect of long distance movements in keeping North and South of Sweden highly inter-connected (29). …”
Section: Discussionsupporting
confidence: 75%
“…This confirmed that epidemic size was mainly driven by infected cattle farms. It also confirmed the expected effect of long distance movements in keeping North and South of Sweden highly inter-connected (29). …”
Section: Discussionsupporting
confidence: 75%
“…This may be partially attributed to the introduction of new animals into the herd or area via animal trade. Indeed, data showed that cattle trade was maintained at a considerable level in Sweden31. Therefore, frequent animal trade in Sweden would increase the heterogeneity of C. parvum IId subtypes on farms and the complexity of infections.…”
Section: Discussionmentioning
confidence: 99%
“…Dublin or S . Typhimurium may be a reflection of the clustering of cattle movements in Sweden [15], where the largest number of movements occur within the same geographical region. These two types of salmonella are the most commonly detected in Swedish cattle [6] and the main route of spread between herds would be expected to be via livestock trade.…”
Section: Discussionmentioning
confidence: 99%